PENGARUH PEMBEBANAN TERHADAP ARUS MOTOR EG-530AD-2F - Zaenal Arifin (Jurnal DISPROTEK, 2019)
All processes that work must be controlled by a system that can be controlled with the aim of increasing efficiency and minimizing the risk of errors. Likewise the production process with a system that can be controlled, in this case in the process of separating goods based on certain criteria as needed with PLC as the basis of control will make a combination of a complex and interrelated system to improve the performance of the system. Analysis of loading prototype of a separator system based on PLC-based altitude, with a power supply voltage of 12 Volt DC to run a prototype system, it was found that the load that can be passed on each data conveyor loading on 12volt dc motor conveyor performance eg-530ad-2f is a load starting from 10-120 gr where the drive used is a 12 Volt DC motor with coupled by a 5mm elastic rubber van, with overall required current of 2.15 A, the required voltage is 12Vdc ± 8.99%.